2017
DOI: 10.1097/md.0000000000004969
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association of MMP-1 gene −1607 (2G/1G) and −519 (A/G) polymorphisms with the risk of osteomyelitis

Abstract: To investigate the effects of matrix metalloproteinase-1 (MMP-1) gene polymorphisms on the onset of osteomyelitis in Chinese Han population.In all, 80 osteomyelitis patients (case group) and 81 healthy people (control group) were recruited into this case-control study. Polymerase chain reaction-restriction fragment length polymorphism method was utilized to examine the genotypes of MMP-1 polymorphisms (−1607 2G/1G and −519A/G) in the 2 groups. Genotype and allele differences between the case and control groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Seven studies have reported the associations between SNPs and three types of osteomyelitis (posttraumatic, hematogenous, and vascular insufficiency-related bacterial osteomyelitis; Asensi et al, 2003;Montes et al, 2006;Valle-Garay et al, 2013;Jiang et al, 2016;Hou et al, 2018;Perez-Is et al, 2019;Zhao et al, 2020). The other three studies have reported the relationship of SNP with unspecified types of bacterial osteomyelitis (Ocana et al, 2007;Tsezou et al, 2008;Kong et al, 2017). This systematic review involved 1,248 patients with bacterial osteomyelitis, including 719 patients with posttraumatic bacterial osteomyelitis, 190 patients with hematogenous bacterial osteomyelitis, 98 patients with vascular insufficiency-related bacterial osteomyelitis, and 241 patients with unspecified types of bacterial osteomyelitis.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies have reported the associations between SNPs and three types of osteomyelitis (posttraumatic, hematogenous, and vascular insufficiency-related bacterial osteomyelitis; Asensi et al, 2003;Montes et al, 2006;Valle-Garay et al, 2013;Jiang et al, 2016;Hou et al, 2018;Perez-Is et al, 2019;Zhao et al, 2020). The other three studies have reported the relationship of SNP with unspecified types of bacterial osteomyelitis (Ocana et al, 2007;Tsezou et al, 2008;Kong et al, 2017). This systematic review involved 1,248 patients with bacterial osteomyelitis, including 719 patients with posttraumatic bacterial osteomyelitis, 190 patients with hematogenous bacterial osteomyelitis, 98 patients with vascular insufficiency-related bacterial osteomyelitis, and 241 patients with unspecified types of bacterial osteomyelitis.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Serum C-reactive protein (p = 0.017) and IL-6 (p = 0.006) levels were significantly higher in patients with posttraumatic osteomyelitis accompanied with the GG genotype, instead of the CG genotype. Kong et al (2017) have concluded that the G allele of rs1144393 in the MMP1 gene was regarded as a genetic risk factor and carriers of the GG genotype have an increased risk of osteomyelitis.…”
Section: Protein Receptor and Enzymementioning
confidence: 99%
“…Recently, growing evidence has shown that single nucleotide polymorphism (SNP) also plays an important role in OM development. Several SNP sites have been found to be associated with the risk of OM development, such as rs16944, rs2234663, rs1143627, rs4251961, and rs1800796 (interleukin, IL genes) ( Alves De Souza et al, 2017 ; Jiang et al, 2020b ), rs45567233 (cathepsin G, CTSG gene) ( Pérez-Is et al, 2019 ), rs1799750, and rs1144393 (matrix metalloproteinase-1, MMP-1 gene) ( Kong et al, 2017 ), implying SNPs participate in OM pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] CRP and ESR are currently used in all patients suspected of having VO; however, they lack the accuracy to differentiate between patients with and without VO. [ 4 ] Anti-glucosaminidase IgG, [ 9 ] iron-regulated surface determinant protein B, [ 10 ] CCL11/eotaxin, [ 11 ] interleukin-6, [ 11 ] S100 calcium binding protein A11, E-selectin, and matrix metalloproteinase-1 [ 12 ] have been reported as potential biomarkers [ 13 ] ; yet, they have not been used for the clinical diagnosis of VO. A review of the literature, employing a data mining approach using Open Targets Platform ( https://www.targetvalidation.org/ ), [ 14 ] presented a list of VO-associated antigens showing elevated autoantibody responses [ 14 ] ; the results are shown in Supplemental Digital Content (Appendix 2, which lists open target database).…”
Section: Introductionmentioning
confidence: 99%